Temperature dependence of protein-water interactions in a gated yeast aquaporin - Aponte-Santamaria, Camilo (Scientific reports, 2017)
Regulation of aquaporins is a key process of living organisms to counteract sudden osmotic changes. Aqy1, which is a water transporting aquaporin of the yeast Pichia pastoris, is suggested to be gated by chemo-mechanical stimuli as a protective regulatory-response against rapid freezing. Here, we tested the influence of temperature by determining the X-ray structure of Aqy1 at room temperature (RT) at 1.3 Å resolution, and by exploring the structural dynamics of Aqy1 during freezing through molecular dynamics simulations. At ambient temperature and in a lipid bilayer, Aqy1 adopts a closed conformation that is globally better described by the RT than by the low-temperature (LT) crystal structure. Locally, for the blocking-residue Tyr31 and the water molecules inside the pore, both LT and RT data sets are consistent with the positions observed in the simulations at room-temperature. Moreover, as the temperature was lowered, Tyr31 adopted a conformation that more effectively blocked the channel, and its motion was accompanied by a temperature-driven rearrangement of the water molecules inside the channel. We therefore speculate that temperature drives Aqy1 from a loosely- to a tightly-blocked state. This analysis provides high-resolution structural evidence of the influence of temperature on membrane-transport channels.